What Is Missiology? - Langmead, Ross (Missiology, 2014)
Should missiology seek the status of a theological discipline? After a brief account of the history of academic missiology it is argued here that a trinitarian missiology is at the heart of all of theology. Missiology should both permeate theology and exist as a subject area to accompany missionary praxis, making theological education at least missiological to the core, if not itself missional. Missiology is part of practical theology, praxis-based and oriented to specific contexts. It draws on both theological and other disciplines (particularly the social sciences) as an interdisciplinary enterprise rather than as a discipline in its own right.